(untitled) (Research, Society and Development, 2020)
This study aims, through the analysis of recent scientific articles, to present the main clinical and laboratory characteristics of the disease caused by SARS-CoV-2 (COVID-19). It is a qualitative bibliographic review that is based on the production based on studies already published in order to analyze different positions in relation to a given subject. The search for the texts was carried out using the following keywords indexed in the DECs (Health Sciences Descriptors): “Respiratory Disease”, “Covid-19”, “Symptoms” and “Laboratory Diagnosis”, on the Science Direct and NCBI platforms (National Biotechnology Information Center) between the years 2019 and 2020. The spread of the disease by SARS-CoV-2 has already infected more than 100,000 people in 100 countries, being considered a pandemic as a result of the epidemiological criteria reached. Due to global contamination, it is necessary to prepare health systems to face the pandemic. Countries exposed to COVI-19 infection must adopt containment measures to prevent the spread of the virus, as is the case in China, which has reduced new cases by 90%. Laboratory diagnosis is extremely necessary to distinguish COVID-19 infection from other diseases. Due to the high capacity for dissemination, social isolation is necessary to prevent the development of new cases, allowing a greater opportunity for the health system to develop vaccines and specific treatments against the virus.